Feminist evaluation and research : theory and practice - Brisolara, Sharon; Seigart, Denise M., 1958-; SenGupta, Saumitra (The Guilford Press, 2014)
This thought-provoking book explores the 'whats, ' 'whys, ' and 'hows' of integrating feminist theory and methods into applied research and evaluation practice. Illustrative cases drawn from U.S. and international studies address a range of social and health issues. The book provides an overview of feminist theory and research strategies as well as detailed discussions of how to use a feminist lens, practical steps and challenges in implementation, and what feminist methods contribute to research and evaluation projects. Reflections at the close of each section invite the reader to consider key.